East Kalimantan Economic Growth In 2019-2023 - Susilo, Joko Hadi; Sari, Shafira Niken; Putri, Intan Firnanda (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
The purpose of this study was to determine the influence of road infrastructure, electricity, education, and health on economic growth between districts and cities in East Kalimantan Province in 2019-2023. This research method uses a descriptive quantitative analysis approach, the data used is sourced from secondary data with the type of panel data for 5 years obtained from the Central Statistics Agency of East Kalimantan and the Directorate General of Financial Balance. The population in this study is Regencies and Cities in East Kalimantan Province. The sampling technique was carried out using saturated sampling so that the number of samples in this study was obtained 50 observation data. The results of this study found that road infrastructure has a significant positive effect on economic growth. Electricity infrastructure has a significant positive effect on economic growth. Educational infrastructure has a positive effect on economic growth. Keywords: Economic Growth, Infrastructure, Data Panel.